Introducing Transport "Surprises" in the Classroom: The Visible Fracture. Issue 3 (1st April 2019) - Cardiff, Michael; Heinle, Ben
Abstract: Heterogeneity in aquifer properties, and the influence of transport processes other than advection and dispersion, often produce transport "surprises" in that measurements become difficult to reconcile with predictions from the traditional advection‐dispersion equation (ADE) that students are introduced to early in their hydrogeology training. Students should be aware of and prepared for the reasons why the ADE (as commonly applied) may not always "work" in the sense of generating valid predictions. Though the predictive limitations of the ADE have been frequently discussed in the hydrogeologic literature, our experience is that students are not appropriately skeptical of transport predictions. For this reason, we believe it is imperative that future generations of hydrogeologists are introduced to transport surprises early in their formative education. We present a laboratory activity, centered around a "Visible Fracture, " which was presented in a laboratory class period of 75 min. The Visible Fracture consists of two sheets of Plexiglas surrounding a heterogenous fluid‐filled aperture. Heated fluid is injected into the fracture, and thermochromic liquid crystal (TLC) materials are used to visualize the temperature both in the flowing fluid and in the surrounding Plexiglas "host rock." Visualization of the plume shows the complex shapes that can be produced due to macroscopic heterogeneity. Tracer particles within the fracture allow students to examine heterogeneous local advective velocities, and to observe retardation of the fluid temperature plume. Student self‐reported knowledge surveys indicate greater conceptual understanding of transport non‐idealities after experiencing this activity. Abstract : Article impact statement : Classroom transport surprises help young hydrogeologists appreciate the multitude of reasons why groundwater transport predictions can fail.